Trends in out of pocket payments and catastrophic health expenditure in the Kyrgyz Republic post "Manas Taalimi" and "Den Sooluk" health reforms, 2012-2018 - Mariia Iamshchikova; Roman Mogilevskii; Michael Nnachebe Onah (BMC, 2021)
Abstract Background Over the years, the Kyrgyz Republic has implemented health reforms that target health financing with the aim of removing financial barriers to healthcare including out-of-pocket health payments (OOPPs). This study examines the trends in OOPPs, and the incidence of catastrophic health expenditure (CHE) post the "Manas Taalimi" and "Den Sooluk" health reforms. Methods We used data from the Kyrgyzstan Integrated Household Surveys (2012-2018). Population-weighted descriptive statistics were used to examine the trends in OOPPs and CHE at three thresholds; 10 percent of total household consumption expenditure (Cata10), 25 percent of total household consumption expenditure (Cata25) and 40 percent of total household non-food consumption expenditure (Cata40). Panel and cross-sectional logistic regression with marginal effects were used to examine the predictors of Cata10 and Cata40. Findings Between 2012 and 2018, OOPPs increased by about US $6 and inpatient costs placed the highest cost burden on users (US $13.6), followed by self-treatment (US $10.7), and outpatient costs (US $9). Medication continues to predominantly drive inpatient, outpatient, and self-treatment OOPPs. About 0.378 to 2.084 million people (6 - 33 percent) of the population incurred catastrophic health expenditure at the three thresholds between 2012 and 2018. Residing in households headed by a widowed or single head, or residing in rural regions, increases the likelihood of incurring catastrophic health expenditure. Conclusions The initial gains in the reduction of OOPPs and catastrophic health expenditure appear to gradually erode since costs continue to increase after an initial decline and catastrophic health expenditure continues to rise unabated. This implies that households are increasingly incurring economic hardship from seeking healthcare. Considering that this could result to forgone expenditure on essential items including food and education, efforts should target the sustainability of these health reforms to maintain and grow the reduction of catastrophic health payments and its dire consequences.